The Development of Physics Teaching Aids to Demonstrate the Intensity of Blackbody Radiation As a Function of Temperature - Hartono Bancong; Ana Dhiqfaini Sultan; Subaer Subaer; Muris Muris (Universitas Muhammadiyah Makassar, 2019)
The purpose of this study was to develop teaching aids of blackbody radiation experiment and practicum devices based on modified free inquiry which are valid and reliable. This teaching aids was designed to demonstrate the relationship between the intensity of radiation and the absolute temperature of a blackbody (the law of Stefan-Boltzmann). The principle of this experiments is the amount of current will flow from the voltage source and enter to the black box. The black box will absorb and emit radiation. There is a nichrome wire inside the black box that will be light up, heat and emit radiation when electrically flowed. The emitted heat will be measured by temperature sensors using thermocouple located outside the black box. Based on experts and practitioner evaluation, the developed teaching aids of blackbody radiation experiment and practicum devices based on modified free inquiry were found to be valid, and reliable. The results of the experiment showed that the intensity of blackbody radiation was directly proportional to its temperature. This result is consistent with the law of Stefan-Boltzmann. Furthermore, the average of students’ perception of the developed teaching aids and practicum devices of blackbody radiation are 74.92% (good) and 80.17% (very good) respectively. This indicates that the teaching aids and practicum devices that have been developed can be used to demonstrate and prove the modern physics concepts related to blackbody radiation.Keywords: Teaching Aids, Stefan-Boltzmann’s law, Blackbody RadiationPenelitian ini bertujuan untuk mengembangan alat peraga eksperimen radiasi benda hitam dan perangkat praktikum fisika berbasis modified free inquiry yang valid dan reliabel. Alat peraga tersebut dirancang untuk mendemonstrasikan hubungan antara intensitas radiasi benda hitam dengan suhu mutlak yang dipancarkannya (Hukum Stefan-Boltzmann). Prinsip kerja dari alat peraga tersebut adalah arus akan mengalir dari sumber tegangan dan masuk ke dalam kotak lubang hitam. Kotak ini berfungsi untuk menyerap dan memancarkan radiasi. Di dalam kotak terdapat kawat nicrom yang akan menyala dan memancarkan radiasi ketika dialiri arus listrik. Panas yang dipancarkan akan diukur oleh termokopel radiasi yang berada di luar kotak. Berdasarkan penilaian validator, alat peraga eksperimen radiasi benda hitam dan perangkat praktikum fisika berbasis modified free inquiry yang telah dikembangkan dinyatakan valid dan reliabel. Hasil uji coba menunjukkan bahwa intensitas radiasi yang dipancarkan oleh benda hitam berbanding lurus dengan temperaturnya yang sesuai dengan hukum Stefan-Boltzmann. Selanjutnya, rata-rata persepsi praktikan terhadap alat peraga eksperimen radiasi benda hitam dan perangkat praktikum yang telah dikembangkan secara berturut-turut adalah 74,92% (baik) dan 80,17% (sangat baik). Hal ini mengindikasikan bahwa alat peraga dan perangkat praktikum yang telah dikembangkan dapat digunakan untuk mendemonstrasikan dan membuktikan konsep-konsep fisika modern yang berhubungan dengan radiasi benda hitam.Kata kunci: Alat Peraga, Hukum Stefan-Boltzmann, Radiasi Benda Hitam